An examination of major works for wind band and brass ensemble: “Incidental suite” by Claude T. Smith, “Concerto for 23 winds” by Walter S. Hartley, and “Fanfare for la Peri” by Paul Dukas - Feyes, Andrew Dean (Kansas State University, 2007)
The following report is research and analysis from the comprehensive examination question based on the Graduate Conducting Recital of Andrew D. Feyes. The recital, performed by the Kansas State University Symphony Band, was given in McCain Auditorium on the campus of Kansas State University on March 13, 2007 at 7:30pm. The repertoire included Fanfare for La Peri, by Paul Dukas, Concerto for 23 Winds, by Walter S. Hartley, and Incidental Suite, by Claude T. Smith. This examination contains thorough theoretical and historical analyses of the included literature. The report also includes the procedures of planning and performing the graduate conducting recital.
Keywords: Claude T. Smith; Incidental Suite; Paul Dukas; Fanfare for La Peri; Walter S. Hartley; Music (0413)